EFFECTIVENESS OF APPLYING PRINCIPLES OF LEGAL CERTAINTY OF JUSTICE IN THE HANDLING OF CRIMINAL CASE - ELif Acar; Sugeng Sudrajat (Jurnal Pembaharuan Hukum, 2018)
The effectiveness of judges' verdict in the trial should ideally contain aspects of the rule of law, justice and expediency. In its implementation is not easy to synergize these three aspects, especially the aspect of legal certainty and fairness are usually contradictory. The results showed that the judge in examining and deciding cases not forever fixated on one principle alone. Constraints faced by judges tend to rule of law in deadlock when written provisions can not answer the problems that exist. Emphasis is more inclined to the principle of justice means should consider a law in society, which is made up of customs and unwritten laws. Judge within reason and legal considerations must be able to accommodate all the provisions that live in the community in the form of customs and unwritten laws. Emphasis tends to be on the principle of expediency over economic nuances.